The acceptance of digital library: a study among the library staffs in UiTM northern branches / Muhammad Shukri Yaakub - Yaakub, Muhammad Shukri (Faculty of Information Management, 2011)
The rapid growth of ICT has given a huge impact in the library operation. Nowadays not only libraries but all are depending on the ICT in their operation. The introduction of digital library in 1990 has provided a new direction in the library operation. The digital library has changed several aspects of traditional library by which it holds the collection in the form of electronic such as e-journal and e-book. In addition, Integrated Library System is also used along with various related technology. However, this new advanced technology in library is still at its early implementation in Malaysia and only the academic libraries have taken initiative towards it in order to support the teaching and learning process. However, there seems to be a shortage in staff acceptance toward digital library, therefore this study intends to investigate the level of acceptance toward digital library at UiTM branches in Northern area that cover two branches which are UiTM Permatang Pauh, Pulau Pinang and UiTM Merbok, Kedah. This research will study the relationship between the independent variable which is perceived ease of use, perceived usefulness, resistance to change and computer literacy toward the dependent variable which is staff acceptance toward digital library.